A striking new species of Blepharis (Acanthaceae) from north-eastern Somalia - Baldesi, Giacomo; Vollesen, Kaj (Phytotaxa, 2022)
Blepharis eilensis (Acanthaceae) is described as new to science. Blepharis eilensis belongs to subg. Acanthodium sect. Acanthodium. It is endemic to north-eastern Somalia, in the Nogal (Nugaal) region and is presently known only from the type collection. The species is compared with similar species from NE Africa (B. forgiarinii, B. diplodonta) and preliminary information on the ecology, distribution and conservation status of this new species is provided.